Stable disease or complete response?: A critical evaluation of the radiologic response to immune checkpoint blockade in advanced melanoma Stabile Erkrankung oder vollständiges Ansprechen?: Evaluation der radiologischen Interpretation des Therapieansprechens auf Immune-Checkpoint-Blockade im metastasierten malignen Melanom - Tietze, J. K.; Heppt, M.; Angelova, D.; Ruzicka, T.; Berger, F.; Berking, C. (Hautarzt, 2017)
Background: Rating the response of melanoma to immune checkpoint blockade (ICB) by conventional CT proves to be difficult, since response patterns and kinetics differ from the classical responses seen with other therapies. Hence, immune-related response criteria were developed. However, they are mainly based on the alteration of the diameter of lesions over time but do not include metabolic activity. Objective: The aim of this study was to search for additional criteria to improve the interpretation of the radiologic images of patients with metastatic melanoma after ICB. Materials and methods: We retrospectively analysed 7 patients with metastatic melanoma over a period of 13–41 months after treatment with ICB using contrast enhanced CT scans from the neck region to the lower abdomen and compared the results in the follow ups with 18F-FDG PET/CT. Results: Metastatic lesions in 5 of 7 patients rated as stable disease (SD) in CT staging showed no metabolic activity in 18F-FDG PET/CT. The size of these lesions did not increase or show metabolic activity in the further follow-up, even after discontinuation of ICB. In contrast, tumor lesions in the other 2 patients rated as SD in CT staging showed metabolic activity in 18F-FDG PET/CT. These tumor lesions expanded significantly in the further course of the disease. Conclusion: In addition to the size of a tumor lesion, its metabolic activity adds important information regarding treatment response. Thus, we propose that the metabolic activity assessed with 18F-FDG-PET/CT should be included in the immune response criteria. No FDG uptake in a lesion should be rated as inactive tumor rather than SD and further treatment may not be required.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Computed tomography; Ipilimumab; Metabolic activity; Pembrolizumab; Positron emission tomography; Stable disease